An integrative approach identifies dysregulated long non-coding RNAs as microRNA decoys during nevus to melanoma transformation. Issue 6 (December 2020) - Chang, Li-Wei; Badal, Brateil; Lu, Ching-Jung; Solovyov, Alexander; Greenbaum, Benjamin D.; Celebi, Julide Tok
Abstract : Mounting evidence supports a role for dysregulated long non-coding RNAs (lncRNA) in the development of many cancers. A recently discovered function of lncRNAs is to act as microRNA (miR) decoys or competing endogenous RNAs, which sequester specific miRs and relieve negative regulation of mRNA expression by miRs. Although a large number of non-coding RNAs are thought to function as competing endogenous RNAs, miR-sequestering lncRNAs involved in nevus to melanoma transformation remain largely unknown. In this study, we applied a bioinformatics approach to a unique dataset of benign melanocytic nevi and primary melanomas of the skin in order to fill this research gap. We modified a previously published miR target prediction algorithm, RNAhybrid, and improved its search efficiency. We reported the presence of many lncRNAs and miRs deregulated when transitioning from a senescence-like state of nevi to melanoma. We provided evidence of a relatively new and understudied mechanism of gene regulation during this process and identified for the first time lncRNAs ( n = 122) that may potentially function as miR decoys as well as their target miRs during nevus to melanoma transformation. The knowledge presented here can be employed for developing biomarkers for diagnostic and risk stratification purposes. Abstract : Supplemental Digital Content is available in the text.